EVALUATION ON METHODS FOR IDENTIFICATION OF VIBRIO SP.: KAWAKAWA (EUTHYNNUS AFFINIS) BRINING SHREDDED AND CHITOSAN ADDITION AS PRESERVATIVE - Purwaningtyas Kusumaningsih (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2021)
The kawakawa (Euthynnus affinis) brine salting that used to make shredded were preservative with salt. Salt addition has aim to inactivate of bacterial contamination. Obviously, bacteria is still capable of growing in kawakawa brine shredding Therefore, in this study chitosan was added as antibacterial in shredded processing. Vibrio sp., is one of common halophilic bacteria found in seafood. If this bacteria is consumed, it can cause serious problems in human health. The objective of this study was to evaluate the factors that affect in identifying Vibrio sp., on kawakawa brine shredding (C), shredded non-chitosan (FC) and shredded contain of chitosan (FC+). The methods evaluated were steps in enriching bacteria, culturing bacterial in selective media and analysing bacterial by API 20E kit. Enriching and incubation periods were needed by halophilic bacteria to adaptation in new environment. It was required to observe the bacteria characteristics' that would be isolated. Bacterial colonies were growth on Thiosulphate citrate bile salt sucrose (TCBS)  were not Vibrio sp., but confirmed as Pseudomonas luteola and Proteus vulgaris based on API 20E analysis. It was showed that TCBS media had some advantages in identifying Vibrio sp. In conclusion, to get the best result in identifying bacteria, at least two  or more methods were used to avoid misidentification.